The DEA Method in Managing the Credit Risk of Companies - Feruś, Anna (Ekonomika, 2008)
The subject of the present paper is a new procedure of forecasting credit risk to companies in the Polish economic environment. What favors the suggested approach is the fact that in Poland, unlike in western countries, the DEA method has not yet been implemented in assessing credit risk faced by companies. The research described in the paper has been conducted on the basis of comparing the proposed DEA method with the currently used procedures, namely the point method, discriminative analysis and linear regression. To verify and compare the efficiency of various methods of company credit risk estimation, the efficiency of the classification of companies has also been examined. The study has involved an analysed sample (a teaching sample) as well as a test sample which was not taken in model building. To conclude, the DEA method facilitates forecasting financial problems, including bankruptcy of companies, in Polish economic conditions, and its efficiency is comparable to or even greater than that of the approaches implemented so far.